Inclusive Schools: Between Justice and School Unpreparedness (Case Study at SMPN 10 Pekalongan) - Faitursina, Ameliani; Wardhani, Novia Wahyu (Jurnal Penelitian Pendidikan, 2025)
The concept of inclusive schools has the goal of realizing justice for all students. By providing opportunities for joint and equal learning in regular schools. However, the practice of inclusive schools still faces many challenges, especially from the factor of school readiness. This study analyzes the application of the value of justice in the implementation of the inclusion school policy at SMPN 10 Pekalongan as well as the role of the Pekalongan City Education Office in striving to implement the value of social justice. This research uses a qualitative approach with a case study method. Data were obtained through interviews with guidance and counseling teachers and the Principal of SMPN 10 Pekalongan, education staff of the Education Office, and psychologist of H. A. Zaky Djunaid Hospital, observations were made at school, and during the process of mentoring students, as well as analysis of policy documents. The data obtained in the field was analyzed using the Miles and Huberman analysis method. The results of the study show that although schools have made good efforts to implement inclusive school policies, there are still obstacles, such as limited facilities, lack of funding and professional personnel, and there is still an inappropriate perception of education and the concept of inclusive schools from some parents. This unpreparedness has an impact on the effectiveness of inclusive learning and the welfare of students with special needs. A comprehensive strategy is needed, including teacher capacity building, provision of adequate facilities, and collaboration with stakeholders to ensure inclusive education truly embodies justice for all learners.